The Family's Role in Early Childhood Moral and Spiritual Development - Aisyah Putri; Dinda Arisha; Alya Salsabilah; Rusda Salimah; Sandi Pradana (Madiha Press, 2025)
The role of the family in shaping the moral and spiritual values of early childhood is crucial, as the family serves as the primary foundation for a child's character development. Children spend a significant amount of time with their families, particularly parents, who are their first role models in learning values, ethics, and the meaning of life. This study aims to explore how families influence the formation of moral and spiritual values in early childhood at home and identify factors that strengthen and hinder this process. Using a qualitative approach, data were collected through in-depth interviews with 15 parents in Hutaimbaru Village, Padangsidimpuan, who have young children. The findings indicate that parents actively instill moral and spiritual values in their children through modeling, habituation, and guidance, recognizing that young children tend to imitate their parents' behaviors. However, challenges arise from external influences such as technology, gadget use, and peer interactions, which can affect children's behavior. When children exhibit deviant behavior, parents tend to respond with corrective measures through empathetic approaches, such as engaging in constructive dialogues. With a holistic and collaborative approach, it is hoped that children can grow into individuals with strong moral and spiritual character.